Diagnóstico arquivístico da seção de arquivo da Assembleia Legislativa do Estado do Pará - ROSA, Shirlene Tatiane Ribeiro (2018)
The present study aims to show an Archival diagnosis of the Archive section of the Legislative Assembly of the State of Pará. In methodological terms, it is an empirical research, adopted as techniques: interview with open questions applied in the Archive Section. The analysis of the collected data followed qualitative procedures, this research is characterized by Case study. And based on the collected data was sought identify the characteristics of ALEPA's Archive to present the main documental typologies found, to propose recommendations for the preservation of documents for the improvement of ALEPA's Archive and justify the need to have a Records Management program to assist in the activities carried out, therefore, the produced and received documents are essential to the Administration for decision making and also to provide citizens' access to public information.